RECENT AVIFAUNISTIC ANALYSIS IN THE FLOODPLAINS OF THE KARA YERTIS (BLACK IRTYSH) AND YERTIS RIVER IN THE PAVLODAR REGION (Experimental biology, 2024)
This research focuses on studying the avian populations in the floodplains of the Kara Yertis (Black Irtysh) and Yertis River in the Pavlodar region, Kazakhstan. There are notable gaps in our understanding of the avifauna in these areas, highlighting the need for continued ornithological research. The primary goal is to address these limitations, with a focus on the Zaysan depression in the East Kazakhstan region and the Pavlodar region. Global climate change and anthropogenic impacts, such as hydroelectric power stations and reservoir construction, are identified as potential contributors to environmental changes in the region. One significant impact is the potential shift in the timing of spring nesting due to climate change, affecting different bird species in varying ways. To investigate these dynamics, field studies were conducted in May and June of 2023, covering seven sites along the Kara Yertis and Yertis River in the Pavlodar region. The study adhered to standardized protocols, taking into account the phenological aspects of bird life cycles. The density of bird species was estimated using route accounting on permanent inventory plots. The study identified a total of 127 bird species across 16 orders in the two model areas. This included species listed in the Red Book, highlighting the importance of conservation efforts. In the Irtysh River of the Pavlodar region with a high humidity level, compared with the Kara Yertis, there were fewer anthropogenic impacts and more bird species (103 species). This study shows that, taking into account climate change and anthropogenic impacts, it is necessary to constantly monitor this region and develop conservation and adaptation strategies.
Keywords: Birds; Avifauna; Biodiversity; Yertis River; Zaysan depression; Kara Yertis; Pavlodar region; Black Irtysh